2018
DOI: 10.7326/m17-1094
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Free Remission After Second-Line Nilotinib Treatment in Patients With Chronic Myeloid Leukemia in Chronic Phase

Abstract: Novartis Pharmaceuticals Corporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
1
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 25 publications
9
117
1
15
Order By: Relevance
“…An increase in the numbers of patients with MS pain was reported in patients treated with frontline nilotinib in the ENEST freedom trial (Hochhaus et al , ; Ross et al , ). However, this study was not designed to describe the painful syndromes that could be considered as WS, and the collection of cases over a 48‐week period remains questionable (Mahon et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the numbers of patients with MS pain was reported in patients treated with frontline nilotinib in the ENEST freedom trial (Hochhaus et al , ; Ross et al , ). However, this study was not designed to describe the painful syndromes that could be considered as WS, and the collection of cases over a 48‐week period remains questionable (Mahon et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The GFR estimating equation was based on the creatinine filtration marker and developed by the Modification of Diet in Renal Disease study group [18, 19]. For T2DM subjects, albumin creatinine ratio (ACR), serum creatinine, cholesterol profile and HbA1c were obtained at the time of initial visit or within the previous 6–12 months from subject medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Eighteen patients achieved a second DMR after a median interval of 2.5 months (range, 1-18 months), and 6 patients are currently in MMR after having resumed a TKI for a median of 3 months. [2][3][4][5][6][7][8][9][10] One patient died of pancreatic cancer during follow-up while in DMR.…”
Section: Treatment-free Remission By Transcript Typementioning
confidence: 99%
“…Recently, the pivotal study STIM1 (Stop Imatinib) demonstrated that patients with CML who had a sustained DMR (sDMR) could safely stop TKI treatment, and approximately 40% of them did not develop recurrent CML or a molecular relapse and did not need to restart TKI, remaining in so‐called “treatment‐free remission” (TFR) after long‐term follow‐up . Several studies have confirmed the possibility of maintaining a TFR either at the DMR level or, more recently, at the MMR level after TKI discontinuation in a proportion of patients ranging from 40% to 60% . Hence, the possibility of permanently stopping CML treatment has become a realistic and, for many patients, highly desirable objective …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation